The Beautiful Release (Al-Sarāḥ al-Jamīl) in the Holy Qur’an and Its Impact on Family and Social Cohesion: An Analytical and Thematic Study - Fatima Ali Saleh Dhakil (Journal of Libyan Academy Bani Walid, 2025)
This study explores the concept of gracious separation (al-sarāḥ al-jamīl) as presented in the Holy Qur’an, viewing it as an ethical and legislative principle that governs the divorce process in a dignified and respectful manner. The aim is to provide an objective and foundational reading of the Qur’anic texts related to this concept, highlighting its educational and social dimensions and its role in strengthening family bonds and minimizing post-divorce conflicts. The study adopts a descriptive-analytical methodology, drawing on classical exegetical sources and analyzing contemporary family dynamics to offer a comprehensive Qur’anic vision that supports the promotion of a respectful and values-based culture of divorce within society.